The Inadequacies of the System of Documents and Policies to Implement Decision No. 79/2005/QD-TTg of the Prime Minister - Hải, Trần Văn; Hải, Nguyễn Như (VNU Journal of Science: Policy and Management Studies, 2016)
Abstract: This paper analyzes the shortcomings in the system of documents and policies promulgated by ministries, agencies and Northwest provinces in all fields of agriculture, forestry, industry and trade, culture and society, science and technology, etc. Based on that, the article points out the need to synchronize, but not overlap the strategic tasks to ministries and public agencies in order to ensure the comprehensive development goals for Northwest region. Keywords : Shortcomings in the system of documents, policies, Decision No. 79